1991
DOI: 10.1289/ehp.9193133
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenes and tumor-suppressor genes.

Abstract: The functional role of oncogenes in human lung carcinogenesis has been investigated by transfer of activated oncogenes into normal cells or an immortalized bronchial epithelial cell line, BEAS-2B. Transfection of v-Ha-ras, Ki-ras, or the combination of myc and raf into BEAS-2B cells produced tumorigenic cell lines, while transfection of rafor myc alone produced nontumorigenic cell lines. In addition to studying the pathogenic role of oncogenes, we are attempting to define negative growth-regulating genes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 94 publications
(96 reference statements)
0
6
0
1
Order By: Relevance
“…These cells have also been widely used to define conditions under which various agents and oncogenes cause neoplastic transformation. 21-23 Our results show that chronic exposure to SWCNT causes malignant transformation in vitro and tumorigenicity in vivo upon injection of transformed cells into nude mouse. Such data strengthen the safety concern for CNT exposure and support the prudent adoption of prevention strategies and implementation of exposure control.…”
mentioning
confidence: 67%
“…These cells have also been widely used to define conditions under which various agents and oncogenes cause neoplastic transformation. 21-23 Our results show that chronic exposure to SWCNT causes malignant transformation in vitro and tumorigenicity in vivo upon injection of transformed cells into nude mouse. Such data strengthen the safety concern for CNT exposure and support the prudent adoption of prevention strategies and implementation of exposure control.…”
mentioning
confidence: 67%
“…Bronchial epithelial cells were chosen in this study because they are a key target for Cr(VI)-induced tumorigenesis. BEAS-2B cells have been widely used in the literature to define conditions under which various agents and oncogenes cause neoplastic transformation [27] – [29] . They have been shown to exhibit similar characteristics and cellular responses to carcinogens as primary or normal lung cells [30] – [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, high frequencies of LOH on chromosome 17p have been reported in many types of cancer, including EC 25-27. The p53 gene and other possible tumor-suppressor genes are located on 17p, and as such, it is conceivable to consider that 17p's telomere may somehow be implicated in tumorogenesis 28. In addition, Finley et al 11 observed that the loss of 17p was the most common event in Barrett's esophagus, and that this loss was significantly associated with an overall telomere length shortening (r = 0.55; p<0.0001).…”
Section: Discussionmentioning
confidence: 99%